LEVERAGING TECHNOLOGY-DRIVEN INNOVATION THROUGH HUMAN RESOURCE CAPABILITIES TO ACHIEVE COMPETITIVE ADVANTAGE IN SERVICE INDUSTRIES - Yohny Anwar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The increasing adoption of digital technologies has transformed competition in service industries, where human resources play a central role in value creation. While technology-driven innovation is widely recognized as a strategic resource, its contribution to competitive advantage largely depends on the organization’s human resource capabilities. This study examines how technology-driven innovation enhances competitive advantage through the development of service innovation, which reflects the effective utilization of human resource capabilities in service industries. Using a quantitative research design, data were collected from service-sector organizations and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model was assessed for reliability and validity, while the structural model was evaluated using path coefficients, coefficient of determination (R²), effect size (f²), and mediation analysis. The findings indicate that technology-driven innovation has a significant positive effect on service innovation and competitive advantage. Service innovation also significantly influences competitive advantage and partially mediates the relationship between technology-driven innovation and competitive advantage. These results suggest that technological investments generate greater competitive value when they are leveraged through human resource capabilities that support innovative service delivery. This study contributes to the human resource management and strategic management literature by highlighting the role of human resource capabilities as a key mechanism for transforming technology-driven innovation into sustainable competitive advantage. Practically, the findings emphasize the importance of aligning digital transformation initiatives with human capital development in service industries.